Calitatea vieții - numitor comun al problemelor globale - Bălașa, Ana (Calitatea Vieții, 1994)
The interest focussed on this concept of Quality of Life, on its definition, on theoretical researches and practical investigation, had started twenty years ago. The author is presenting an interesting point of view related to the significance of that moment when the quality of life had emerged as a distinct concept. The article is based on an extensive and important bibliography and contains the views and conclusions of a Romanian specialist dedicated to this fundamental concept.